Market, entrepreneurial orientations, and information system use: a systematic literature review / Kazeem Abiodun, Ehsan Fansuree Surin and Azlin Shafinaz Mohamad Arshad - Abiodun, Kazeem; Surin, Ehsan Fansuree; Mohamad Arshad, Azlin Shafinaz (Universiti Teknologi MARA Selangor, 2024)
This ADO-framework-guided systematic literature review looks at the complicated connections between market orientation (MO), entrepreneurial orientation (EO), and the use of information systems (IS). It aims to elucidate the empirical linkages among MO, EO and IS use. Since commercial software was introduced in 1954, entrepreneurs have deliberately integrated IS modules to optimize business processes. The study examines IS development and its impact on company strategies. MO, EO, and IS use are crucial to company success in today's competitive environment. Major IS development players value exceptional modules and argue for tailored solutions to address off-the-shelf system issues. PRISMA and SPAR-4-SLR are rigorously applied to the study in order to identify significant literature contributions. By using Web of Science and Scopus, the process emphasizes strict selection and quality standards. This study illuminates market and entrepreneurial perspectives, particularly concerning IS activities. The literature review offers theoretical guidance for enterprises, policymakers, and IS designers. Stakeholders can support entrepreneurs in integrating IS by aligning strategy with market dynamics, prioritizing user-centric design, encouraging innovation, and adapting to technology. Collaboration between IS developers and entrepreneurs, facilitated by supportive legislation, enables the realization of practical implications for fostering dynamic and resilient digital enterprises. Theoretically, we contend that IS adoption and strategy are contingent upon collaborative efforts in strategic entrepreneurship and marketing. Consequently, we contend that an examination of IS should extend beyond conventional and wellestablished technology acceptability frameworks.